Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1039/c9cc06637c
|View full text |Cite
|
Sign up to set email alerts
|

Using alcohols as simple H2-equivalents for copper-catalysed transfer semihydrogenations of alkynes

Abstract: Copper(i)/N-heterocyclic carbene complexes enable a catalytic transfer semihydrogenation of alkynes employing simple and readily available alcohols such as isopropanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Catalytic transfer hydrogenations represent powerful and mild methods for the reduction of alkene functionality. We believe that mechanistically similar catalytic transfer hydrodeuteration reactions hold much promise for making selectively deuterated small molecules. Until recently, selective catalytic hydrodeuteration reactions were rare and usually employed as mechanistic probes for alkyne semireductions. A major challenge in catalytic transfer hydrodeuteration is discriminating between hydrogen (H) and deuterium (D) for selective incorporation into alkene functionality. , Catalytic alkene transfer hydrodeuteration reactions are now possible on a variety of alkenes. Transition metal catalyzed transfer hydrodeuteration typically occurs in a regioselective manner for unactivated terminal alkenes, but selectivity is generally lower for terminal aryl alkene substrates (Scheme a). Alternatively, using a boron catalyst, highly selective installation of deuterium into activated 1,1-diarylalkenes is possible, but with a limited alkene scope (Scheme b). , …”
Section: Introductionmentioning
confidence: 99%
“…Catalytic transfer hydrogenations represent powerful and mild methods for the reduction of alkene functionality. We believe that mechanistically similar catalytic transfer hydrodeuteration reactions hold much promise for making selectively deuterated small molecules. Until recently, selective catalytic hydrodeuteration reactions were rare and usually employed as mechanistic probes for alkyne semireductions. A major challenge in catalytic transfer hydrodeuteration is discriminating between hydrogen (H) and deuterium (D) for selective incorporation into alkene functionality. , Catalytic alkene transfer hydrodeuteration reactions are now possible on a variety of alkenes. Transition metal catalyzed transfer hydrodeuteration typically occurs in a regioselective manner for unactivated terminal alkenes, but selectivity is generally lower for terminal aryl alkene substrates (Scheme a). Alternatively, using a boron catalyst, highly selective installation of deuterium into activated 1,1-diarylalkenes is possible, but with a limited alkene scope (Scheme b). , …”
Section: Introductionmentioning
confidence: 99%
“…41 As a much more practical and ready available H 2 equivalent, it was recently shown that iso-propanol can also be employed in copper(I)-catalyzed transfer hydrogenations. 42 With a simple NHC/copper(I) complex 22 in catalytic amounts and NaOtBu as a basic additive, internal alkynes 20 could be converted into Z-alkenes 21 in moderate to very good yield (48-96%), while maintaining a high to excellent Z/E ratio (82:18 to 99:1) (Scheme 4, b). Remarkably, even under these drastic conditions, no overreduction to the corresponding alkane was observed, again underscoring the key influence of the NHC ligand on the chemoselectivity.…”
Section: Homogeneous Copper-catalyzed Transfer Hydrogenationsmentioning
confidence: 99%
“…To the best of our knowledge, non-noble metal-catalyzed methods for stereodivergent semi-reduction of alkynes using a CTH strategy are still insufficient, although a few copper-catalyzed semi-reduction of alkynes are known with equivalent amounts of base and limited substrate scope. 12 With our interest in the catalytic systems of transition-metal and diboron compounds, 13 we herein developed the Cu(OAc) 2 -catalyzed semi-reduction of alkynes under the aegis of B 2 pin 2 , and the absolute stereoselectivity of the products depended on the nature of substrates.…”
Section: Introductionmentioning
confidence: 99%